PUBLIC SECRETS. - Gilbert, Jeremy (Cultural Studies, 2007)
The widely-observed degradation of the public sphere in the ‘Western democracies’ has been accompanied by a proliferation of secrecy and secrets of different types. From the ‘privatisation’ of social life to the worrying trend towards unaccountable government, sites for the public legitimation of shared knowledge are in decline while the knowledge economy makes various kinds of ‘secret’ knowledge (software source codes, for example) incredibly valuable. Derrida's reflections on ‘the secret’ provide a useful way in to thinking through the connections between these issues, but it is never entirely clear that he succeeds in his stated aim of rescuing his ‘taste for the secret’ from the obvious charge that it is complicit with a solipsistic logic of privatisation (in every sense of the word). This observation opens up the possibility of a dialogue between Derrida, Levinas, Critchley, Arendt and Nancy around the question of community and relationality which highlights a tension between the potentially individualistic implications of a strand of Levinasian philosophy on the one hand, on the other the commitments of thinkers such as Nancy and Arendt to a thought of irreducible relationality and Cultural Studies’ historic commitment to a practice of public politicisation of previously ‘private’ (indeed, ‘secret’) areas of human experience.